1997
DOI: 10.1093/ajcn/65.4.1034
|View full text |Cite
|
Sign up to set email alerts
|

Changes in body composition and fat distribution after short-term weight gain in patients with anorexia nervosa

Abstract: The most commonly described psychologic abnormality associated with anorexia nervosa is a distorted perception of body weight and shape. This perception may contribute to the anorexic patient's resistance to gaining weight even when it is a medical necessity. The purpose of this study was to assess body-composition and fat-distribution changes after short-term weight gain in 26 female anorexia nervosa patients 27.6 +/- 6.6 (mean +/- SD) y of age, with a body mass index (BMI; in kg/m2) of 16.5 +/- 1.9. They par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(41 citation statements)
references
References 14 publications
4
33
0
4
Order By: Relevance
“…Similar results for subscapular and triceps skinfold were reported by BaracNieto et al (1979) in undernourished adult males undergoing nutritional repletion. A different distribution of the fat during nutritional repletion is also possible (Orphanidou et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results for subscapular and triceps skinfold were reported by BaracNieto et al (1979) in undernourished adult males undergoing nutritional repletion. A different distribution of the fat during nutritional repletion is also possible (Orphanidou et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have evaluated body composition in anorectic patients (Fohlin, 1977;Hannan et al, 1990;Krahn et al, 1993;Scalfi et al, 1993;Nuñiez et al, 1994;Probst et al, 1996;Orphanidou et al, 1997;Polito et al, 1998): a decrease of both fat-free mass (FFM) and fat mass (FM) has always been reported, with lean tissues accounting for a variable percentage of the reduction in body mass. With respect to refed patients, changes in FFM and FM (Orphanidou et al, 1997;Probst et al, 2001), body potassium (Pirke et al, 1986), total body water and its intracellular=extracellular distribution (Vaisman et al, 1988), as well as in bioimpedance analysis (Polito et al, 1998;Scalfi et al, 1999), have been observed after weight recovery.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to refed patients, changes in FFM and FM (Orphanidou et al, 1997;Probst et al, 2001), body potassium (Pirke et al, 1986), total body water and its intracellular=extracellular distribution (Vaisman et al, 1988), as well as in bioimpedance analysis (Polito et al, 1998;Scalfi et al, 1999), have been observed after weight recovery. The studies available in the literature also indicate that FM represents 21 -77% of the weight gained (Russell & Mezey, 1962;Forbes et al, 1984;Pirke et al, 1986;Mitchell & Truswell, 1987;Vaisman et al, 1988;Krahn et al, 1993;Waller et al, 1996;Orphanidou et al, 1997;Polito et al, 1998;Probst et al, 2001;Grinspoon et al, 2001), while the number of calories needed to put down body mass seems to increase during refeeding (Salisbury et al, 1995). Nevertheless, despite the widespread use of anthropometric techniques for the assessment of nutritional status, only a few studies have so far examined the changes in skinfolds and circumferences which occur during weight recovery (Forbes et al, 1984;Nuñez et al, 1994;Orphanidou et al, 1997;Polito et al, 1998;Probst et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Premenarcheal AN, although rare, is well recognised (Gowers et al, 1991;Jacobs & Isaacs, 1986;Bryant-Waugh, 2000). The majority of studies to date looking at body composition in eating disorders have been on postmenarcheal adolescents or adult patients (Vaisman et al, 1988;Mazess et al, 1990;Orphanidou et al, 1997;Trocki & Shepherd, 2000). The physical impact of malnutrition in pre-and peri-pubertal children with eating disorders has been little investigated, the largest series being a retrospective study of 20 adults whose AN was of premenarcheal onset (Russell, 1985).…”
Section: Introductionmentioning
confidence: 99%